基于Inventor的圆柱蜗杆参数化设计 - 乔永钦; 杨顺成; 罗登峰; 牛怡 (Jixie chuandong)
The most of normal cylindrical worm tooth is machined by using straight lines forming tool.As the different installation positions of the tool,the tooth profile shape of the resulting helicoidal surface in the different sections is also different.By using the 3D solid modeling software of Inventor,the process of the straight lines lathe tool cutting worm is simulated,according to the different of installation position of the tool,the different type of cylindrical worm is gotten.The parametric design of worm is realized,the duplication labor of designer is reduced and the efficiency is improved.